2012
DOI: 10.1103/physreve.85.011128
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the microdynamics to the emergent macrovariables: Self-organized criticality and absorbing phase transitions in the deterministic lattice gas

Abstract: We reinvestigate the Deterministic Lattice Gas introduced as a paradigmatic model of the 1/f spectra [Phys. Rev. Lett. 64, 3103 (1990)] arising according to the self-organized criticality scenario. We demonstrate that the density fluctuations exhibit an unexpected dependence on systems size and relate the finding to effective Langevin equations. The low-density behavior is controlled by the critical properties of the gas at the absorbing state phase transition. We also show that the deterministic lattice gas i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…We on the other hand, observe a gradual change of exponents to their mean-field values. Therefore, our results provide evidence for a critical sandpile model with stochastic undirected dynamics which does not belong to the Manna universality class, requiring us to reconsider the controversial concept of universality in sandpile models [51,52]. We close by noting that the mean-field behavior observed in our model is due to an effective range of "interaction" which increases with increasing noise, which underlies the mean-field universality class.…”
Section: Resultsmentioning
confidence: 56%
“…We on the other hand, observe a gradual change of exponents to their mean-field values. Therefore, our results provide evidence for a critical sandpile model with stochastic undirected dynamics which does not belong to the Manna universality class, requiring us to reconsider the controversial concept of universality in sandpile models [51,52]. We close by noting that the mean-field behavior observed in our model is due to an effective range of "interaction" which increases with increasing noise, which underlies the mean-field universality class.…”
Section: Resultsmentioning
confidence: 56%
“…Simulations of this model exhibit 1/f spectra and the dissipation take place on fractal-like structures. However, recently it was realized that the model does not display self-organization to criticality (Giometto and Jensen 2012), but requires tuning to reach the critical point of the (conserved directed percolation) absorbing state phase transition. It is probably fair to say that despite its long history (van der Ziel 1950) 1/f -noise is no longer a motivation for SOC, possibly because of the confusion about its actual meaning (1/f versus 1/f α ) and also the possibility, at least in contemporary computer models, to characterize correlations directly in the time domain rather than indirectly via the power spectrum.…”
Section: Paradigmatic Versus Good Modelsmentioning
confidence: 99%
“…Christensen et al [20] showed 1/f noise in a SOC system with locally non-conservative dynamics. For deterministic lattice gases [21,22], the density-fluctuations show 1/f power-spectrum.…”
Section: Introductionmentioning
confidence: 99%